The Security System For Web-Based Lontar Images in JPG Format Using The Rivest Shamir Adleman - Rianty, Winda; Gede Suhartana, I Ketut (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
The Security System For Web-Based Lontar Images in JPG Format Using the Rivest Shamir Adleman Method is a system that is basically used to secure an image in JPG format, which after the encryption process will be converted into txt. Where the system functions to secure lontar by using an encryption process using a cryptographic technique, namely Rivest Shamir Adleman (RSA) which is expected to help the public to maintain information or documentation and evidence of important events that occurred in the past.